A spiritual care intervention for chaplains in home-based palliative care: design of a mixed-methods study investigating effects on patients' spiritual wellbeing. Issue 3 (3rd July 2022) - Liefbroer, Anke I.; Wierstra, Iris R.; Janssen, Daisy J.A.; Kruizinga, Renske; Nagel, Ineke; Olsman, Erik; Körver, Jacques W.G.
Abstract: Recently, the call for chaplains to become 'research literate' has been recognized by various scholars as well as by practitioners in the field. However, papers that present and discuss the study design and provide guidance on the methodology of chaplaincy research are scarce. The aim of this study is to present the design of a mixed-methods study that investigates the impact of a spiritual care intervention on patients' spiritual wellbeing in palliative, home-based care. It reports on the steps needed to conduct such a study in chaplaincy care, and describes and discusses the study's research design, intervention, participants, sampling strategy, patient and public involvement, procedure, ethical considerations, data collection, and analysis. Presenting and discussing such a design is not only useful for researchers before conducting their study, in order to create transparency, but also for chaplains to improve their knowledge on research methodology and research literacy.